Modélisation d’accompagnement : appropriation de la démarche par différents partenaires et conséquences - Frédérique Chlous-Ducharme; Françoise Gourmelon (VertigO, 2011)
The study describes the implemented approach within the framework of a research-action dealing with interactions between socio-economical and ecological dynamics in a coastal area (Ouessant island, in the west of France). It describes how the companion modelling approach has encouraged the interdisciplinarity. The tools of the companion modelling (multi-agent model, simulations computing, role-playing game) were used to raise awareness with local people in landscape dynamics. Then they were mobilized for students to coastal issues and sustainable development. The scientific knowledge was disseminated by adapting the main research output, to local population and to young people. This was done in association with land managers and educators, and a reflective analysis the commitment of participants in these devices was undertaken. Through this experiment, most participants developed new skills related to interdisciplinarity, cooperation and communication, about the environmental management. This sudy also reveals the difficulties of appropriation of the approach by the partners. The appropriation of the stance of companion modelling seems then central at the same time to constitute a collective, but also to take up developed tools.